Comparative criterion of alternative variants of the freight car park management - Martseniuk, L. V.; Pshinko, O. M. (Science and Transport Progress, 2010)
The article describes the optimal criterion for different variants of management of freight car stocks. The authors came to the conclusion that in order to achieve the biggest profit the variant of reformation with getting the greatest net discount income is most effective.